2021
DOI: 10.31557/apjcp.2021.22.6.1767
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Information Behaviours and Needs among Singapore Women: A Qualitative Study

Abstract: Background: There is growing evidence on cancer communication and its impact on cancer-related health outcomes; however, little is known about how women gain access to and use breast cancer information in the multi-ethnic Asian context. This paper aimed to explore the breast cancer information acquisition behaviours and needs among Singapore women who attended a community-based health organisation for mammography screening. Methods, design and setting: Qualitative data were collected through semi-structured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In addition, NSFs and HCPs lacked trust in women to understand the changing programme, and the current study findings showed that many women did not particularly consider the harms of screening when deciding to attend mammograms. These findings are consistent with research that demonstrates that although most women adhere to screening guidelines, they generally do not know how they were developed and that there are screening harms 33 . Furthermore, research has shown that women require prompting to consider screening harms in low‐risk pathway scenarios, and so, addressing awareness and understanding of the harms is necessary for communicating low‐risk pathways to women 28 …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, NSFs and HCPs lacked trust in women to understand the changing programme, and the current study findings showed that many women did not particularly consider the harms of screening when deciding to attend mammograms. These findings are consistent with research that demonstrates that although most women adhere to screening guidelines, they generally do not know how they were developed and that there are screening harms 33 . Furthermore, research has shown that women require prompting to consider screening harms in low‐risk pathway scenarios, and so, addressing awareness and understanding of the harms is necessary for communicating low‐risk pathways to women 28 …”
Section: Discussionsupporting
confidence: 80%
“…These findings are consistent with research that demonstrates that although most women adhere to screening guidelines, they generally do not know how they were developed and that there are screening harms. 33 Furthermore, research has shown that women require prompting to consider screening harms in low-risk pathway scenarios, and so, addressing awareness and understanding of the harms is necessary for communicating low-risk pathways to women. 28 Despite heightened concerns from the professional stakeholders that women would not receive the change to low-risk pathways well, women in fact had concerns that were less severe than both the HCPs and NSFs.…”
Section: What This Study Adds To the Existing Literaturementioning
confidence: 99%
“…Using gender nuances may simply be an easy excuse to hide the true reasons for non-compliance. That said, more publicity on the whereabouts and availabilities of screening facilities at the national level is needed (Lin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other Asian countries, also reported significant rise of BC in their population. In Singapore, according to the statistics released by National disease registry(2021), between the years 2014 & 2018, 11,232 new cases of BC have been reported and ≥2100 females died of breast cancer, accounting to around 17.3% of cancer related deaths [ 17 , 18 ]. The data also pointed out that it is more prevalent among females from Chinese ethnicity but the worst 5 year survival rate was reported among Malay women(58.5%), with likely younger age at diagnosis, presentation at advanced stages and more aggressive tumor biology in contrast to other ethnic groups of the region[13] [ 18 ].…”
Section: Discussionmentioning
confidence: 99%